Anticipating complexity in the deployment of gene drive insects in agriculture. (24th January 2018) - Baltzegar, Jennifer; Cavin Barnes, Jessica; Elsensohn, Johanna E.; Gutzmann, Nicole; Jones, Michael S.; King, Sheron; Sudweeks, Jayce
ABSTRACT: Insects cause substantial losses to agricultural crops each year and require intensive management approaches. Genetic pest management has emerged as a viable, non-chemical alternative for managing insect pests. The development of engineered gene drives for agricultural use is promising, though unproven, and has the potential to impact farmers as well as broader socio-ecological systems in several ways. Drawing on lessons from the deployment of other pest control technologies, this paper considers how insects containing gene drives could intersect with some of the complexities that characterize agricultural systems. Gene drives are being developed in a landscape of pest management shaped by past and current approaches, experiences, regulations, public opinion, and pest invasions. Because gene drive insects may spread well beyond their release area, stakeholder groups at different spatial scales need to be engaged in decisions about their deployment. This new paradigm both complicates and offers great promise for future pest management efforts.